Peningkatan Kemampuan Membaca Pemahaman melalui Pendekatan Whole Language Siswa Kelas IV UPT SPF SD Inpres Sambung Jawa 1 Kecamatan Mamajang Kota Makassar - Irfiana Maulida Ilyas; Munirah Munirah; Andi Paida (Journal on Education, 2024)
This research aims to determine the increase in reading comprehension skills through a whole language approach for class IV students at UPT SPF SD Inpres Sambung Jawa 1 Mamajang District, Makassar City. This type of research is classroom action research (PTK) which consists of 4 stages, namely planning, implementation, observation and reflection. This research was carried out at UPT SPF SD Inpres Sambung Jawa 1 Mamajang District, Makassar City with 30 class IV students as research subjects. The instruments of this research were an observation sheet and a reading comprehension test. Observation, test and documentation data collection techniques. Data analysis techniques were carried out descriptively, quantitatively and qualitatively. The results of the research showed that there was an increase in the reading comprehension ability of fourth grade students at SD Inpres Sambung Jawa 1 through the whole language approach which can be seen in the percentage of students who completed the first cycle, 63% and in the second cycle, the percentage of students who completed it was 93%.